Forming Cohesive Calcium Oxalate Layers on Marble Surfaces for Stone Conservation - King, H.; Mattner, D.; Plumper, O.; Geisler, T.; Putnis, Andrew (American Chemical Society, 2014)
Batch experiments were conducted with Carrara marble cubes to examine the replacement of calciteby calcium oxalate, a proposed method of protection for marble used as building stone. Coherent oxalate coatings formed on the marble surface during reactions with >10 mM oxalic acid. The replacement rim contained an inner layer that remained attached to the marble surface and was composed of submicron-sized, rounded grains of calcium oxalate with minimal interconnected porosity, although open fluid pathways (inherited grain boundaries from the underlying marble) were present. In contrast, the outer rim comprises large, individual crystals and is easily removed. Raman spectroscopyidentified the mineral in both layers as whewellite (CaC2O4·H2O). Raman mapping revealed that the rims have zones of different crystallographic orientations contributing to the friability of the outer layer. Mapping of 18O incorporation into the replacement rim indicates that the outer layer formed from the inner layer via a fluid-mediated dissolution-reprecipitation mechanism. This suggests that the textures of precipitated oxalates could be tailored to different marble protection applications through changes insolution chemistry.